Public Service Satisfaction on Hajj-Related Services in Indonesia: Demographic Analysis - Fathurrahman, Reza; Abidin, Zaenal; Utami, Anisa Dwi (AL-MUZARA'AH, 2021)
Measurement of public service satisfaction with government services serves as a valuable reflecting point for public officials to improve the public service quality. Pilgrimage to Mecca and Medina in Saudi Arabia is considered as a national duty and government responsibility in countries with a significant number of Muslim citizens. This article analyzes primary data from the 2019 national public service satisfaction survey on hajj-related services within Indonesian territory collected by the Ministry of Religious Affairs to examine variation across demographic backgrounds. 1,491 respondents participated in the survey representing individual appraisals toward various services during departure and returning phases. The main focus of investigation are the six selected service dimensions, namely, 1) Individual capability, 2) Ease of access to information, 3) Service procedures, 4) Speed of service, 5) Facilities and infrastructure, and 6) Cost-related perception. The results of regression analysis support diverse roles of demographic variables in explaining variance in public service satisfaction feedback. The empirical findings suggest that people with a higher-level education are more likely to experience less satisfaction. Meanwhile, females are likely to perceive higher satisfaction with the provided services than the males.